Effect of Produced Formation Water on Soil Nitrifying Bacteria and Earthworms - E. I. Atuanya; G. O. Iserhienrhien; M. J. Emejulu (Journal of Applied Sciences and Environmental Management, 2023)
The research work was carried out to investigate the effects of produced formation water on soil nitrifying bacteria and earthworm using standard methods. The microbial analysis of produced formation water samples showed the presence of Pseudomonas aeruginosa, Bacillus cereus, Micrococcus luteus and Yeast and Aspergillus niger. Physicochemical parameters of produced formation water (PFW) analysed shows neutral pH (6.33), high electrical conductivity (960.6 S/cm), lower than accepted temperature (28.46oC), total dissolved solids (TDS) (756mg/l), dissolved oxygen of 4.6mg/l and higher than accepted of nitrate (52.mg/l), sulphate, lead, chromium, cadmium and copper. The PFW treatment was observed to increase nitrate content and optical density of receiving soil. The treatment progressively decreased the Nitrobacter count across the experimental duration period (seven days) and decreased earthworm survival as the % treatment increases. This study revealed that produced formation water negatively impacts the receiving soil and its organisms in several ways. Hence, regulatory bodies could strengthen its sensitization to the public and private enterprises and the general populace on the damage of discharge of produced formation water.